The impact technique in the works of Shaker Hassan Al Said and Alberto Buri: comparative study - Fadia aqeel jabar (Basrah Arts Journal, 2023)
The current research succeeded in studying the method in which the artist employs interaction with the child through the language of short influence (thank you Hassan and Alberto Buri) as a comparative model only to reveal the method in which they employ everything for his concept of impact in his artwork technically and intellectually. Which were discussed as vocabulary that formed the current studies, which distinguishes four chapters: The first chapter (the general framework of the research): The emergence of the research problem that emerged in the light of the question: What is the nature of presenting the philosophy of impact and the method of its implementation in the work of Shaker Hassan and Alberto Buri? As a comparative study, the researcher then presented the basics of the research framework, including the importance, objectives, limits, and conclusion of the separation of words. The second chapter (theoretical framework and previous studies) came to obtain it Solid structural foundations on which the research is based, and the introduction of methodological and scientific considerations. Which included three sections: The first topic: was devoted to studying the concept of impact in philosophy. The second topic: specialized in studying experimental performances in contemporary art. The topic began with a general introduction that dealt with experience and experience and its role in developing performance in artistic work, and then dealt with a review of some artistic experiences, their transformations and developments. Due to experience and intellectual development, while the third topic included: the experience of the intellectual and technical impact of Shaker Hassan and Alberto Buri, after which the indicators that resulted from the theoretical framework were mentioned. and a review of previous studies, As for the third chapter (research procedures): in it the descriptive approach for the research was chosen, and then the research community was determined from which the sample was taken, as well as the selection of the research tool (observation) to achieve its objectives, then the sample models were analyzed according to a technical vision with philosophical dimensions. As for the fourth chapter (results, conclusions, recommendations and proposals): it included the results reached by the researcher through analyzing the sample and then discussing it, as the conclusions were proven.